Effect of genetic background and postinfectious stress on visceral sensitivity in Citrobacter rodentium‐infected mice. Issue 5 (4th January 2016) - Mondelaers, S. U.; Theofanous, S. A.; Florens, M. V.; Perna, E.; Aguilera‐Lizarraga, J.; Boeckxstaens, G. E.; Wouters, M. M.
Abstract: Background: Infectious gastroenteritis is a major risk factor to develop postinfectious irritable bowel syndrome (PI‐IBS). It remains unknown why only a subgroup of infected individuals develops PI‐IBS. We hypothesize that immunogenetic predisposition is an important risk factor. Hence, we studied the effect of Citrobacter rodentium infection on visceral sensitivity in Th1‐predominant C57BL/6 and Th2‐predominant Balb/c mice. Methods: Eight‐week‐old mice were gavaged with C. rodentium, followed by 1 h of water avoidance stress (WAS) at 5 weeks PI. At 10, 14 days, and 5 weeks PI, samples were assessed for histology and inflammatory gene expression by RT‐qPCR. Visceral sensitivity was evaluated by visceromotor response recordings (VMR) to colorectal distension. Key Results: Citrobacter rodentium evoked a comparable colonic inflammatory response at 14 days PI characterized by increased crypt length and upregulation of Th1/Th17 cytokine mRNA levels ( p uncorrected < 0.05) in both C57BL/6 and Balb/c mice. At 5 weeks PI, inflammatory gene mRNA levels returned to baseline in both strains. The VMR was maximal at 14 days PI in C57BL/6 (150 ± 47%; p = 0.02) and Balb/c mice (243 ± 52%; p = 0.03). At 3 weeks PI, the VMR remained increased in Balb/c (176 ± 23%; p = 0.02), but returned to baseline in C57BL/6 mice. At 5 weeks PI, WAS could not re‐introduce visceral hypersensitivity (VHS). Conclusions & Inferences: Citrobacter rodentium infection induces transient VHS in C57BL/6 and Balb/c mice, which persisted 1 week longer in Balb/c mice. Although other strain‐related differences may contribute, a Th2 background may represent a risk factor for prolonged PI‐VHS. As PI‐VHS is transient, other factors are crucial for persistent VHS development as observed in PI‐IBS. Abstract : Visceral hypersensitivity (VHS) is a hallmark of (postinfectious) irritable bowel syndrome (PI‐IBS) but the underlying mechanisms remain largely unknown. We studied whether immunogenetic background and acute stress in the post‐ Citrobacter rodentium infectious phase influence the development of VHS and found that Citrobacter rodentium infection induces transient VHS in C57BL/6 and Balb/c mice, which persisted 1 week longer in Balb/c mice. Acute stress in the postinfectious phase did not recreate VHS, irrespective of immunogenetic background. View the podcast on this paper at the following sites: iTunes:https://itunes.apple.com/gb/podcast/neurogastroenterologymotility/id1101169138 Youtube:https://www.youtube.com/watch?v=DWNf9Rzt8mI&feature=youtu.be